2018
DOI: 10.1002/prep.201800149
|View full text |Cite
|
Sign up to set email alerts
|

Estimation on the Safe Storage Temperature of Nitrocellulose with Different Humectants

Abstract: In order to estimate the safe storage temperatures of nitrocellulose (NC) with different humectants (water, ethanol, and isopropanol), non-isothermal experiments were performed by a differential scanning calorimeter (DSC). Thermodynamic parameters were simulated by thermal safety software (TSS). Comparison of autocatalytic simulation and nth order simulation was conducted. Also, Kissiger-Akahira-Sunose (KAS) and Ozawa-Flynn-Wall (OFW) methods were employed to validate the simulated activation energy E, whose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…It can be observed that addition of plasticizers (inert and energetic) cause decrease of reaction order in comparison to G(CI)1. Wei et al [56,57] also determined reaction order (n th order with autocatalysis) for pure nitrocellulose and nitrocellulose containing different solvents (ethanol, isopropanol) -the reaction order was in the range from 1.4 to 1.7. The addition of low molecular compounds (plasticizers and stabilizers) to the NC matrix caused increase in the reaction order.…”
Section: Granulesmentioning
confidence: 99%
“…It can be observed that addition of plasticizers (inert and energetic) cause decrease of reaction order in comparison to G(CI)1. Wei et al [56,57] also determined reaction order (n th order with autocatalysis) for pure nitrocellulose and nitrocellulose containing different solvents (ethanol, isopropanol) -the reaction order was in the range from 1.4 to 1.7. The addition of low molecular compounds (plasticizers and stabilizers) to the NC matrix caused increase in the reaction order.…”
Section: Granulesmentioning
confidence: 99%
“…The combustion and explosion behaviors of NC were also in focus 13 , 17 . In addition, a large number of experiments attached great importance to the influence of various catalysts 18 , 19 , stabilizers 20 24 , plasticizers 25 , 26 , wetting agents 2 , 25 , 27 30 , and inorganic salts 31 , 32 on the thermal behaviors of NC.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме традиционных областей применения, НЦ используются при изготовлении высокоэнергетических малочувствительных порохов [2] и новых наукоёмких материалов [3]. Наряду с поиском новых областей применения активно изучаются их свойства [4,5].…”
unclassified